An Equitatable Partnership Model for Natural Resource Investment: Reconciling Capital, Finance, and Community Welfare in Indonesia's Palm Oil Sector - Muhammad Ihsan; Ni Luh Made Mahendrawati; I Gusti Bagus Suryawan; Ni Komang Arini Styawati (Journal Equity of Law and Governance, 2026)
This study develops a transformative partnership model to address structural injustice in the utilization of Indonesia's natural resources, focusing on the palm oil sector. Employing a mixed-method socio-legal approach, it finds that existing partnerships—transactional, labor-based, and the mandated nucleus-plasma scheme—perpetuate colonial and New Order-era inequalities, violating principles of both deontological and teleological justice. A stark welfare paradox is identified: corporate plantation workers remain in low-wage dependency, while independent smallholders in cooperatives achieve significantly higher income and asset ownership. The analysis, framed by Rawlsian and Walzerian theories of justice and New Institutional Economics, reveals that current regulations create high transaction costs and path dependency that favor capital. The proposed model, "Justice as Redistribution and Reciprocal Advantage," advocates for a state-mediated, bank-financed gradual redistribution of corporate land to farmer cooperatives, coupled with corporate transition into downstream industries. This creates a Kaldor-Hicks efficient "win-win" scenario, fulfilling the constitutional mandate for natural resources to serve the people's greatest prosperity. The study concludes that only a radical restructuring of asset ownership and partnership governance can achieve substantive equity.